Pelvic Actinomycosis Mimicking Pelvic Malignancy - Sofia Modesto Saramago; Joana Catarina Cominho; Sara Soares Marques Proença; Pedro João Casado Conde; Filomena Maria Pinheiro Nunes (Revista Brasileira de Ginecologia e Obstetrícia, 2019)
Abstract Asymptomatic female genital tract colonization with Actinomyces spp is not uncommon, particularly among intrauterine device users. Pelvic actinomycosis is an extremely rare disease. The clinical picture can resemble an advanced ovarian malignancy. We report a case of pelvic actinomycosis mimicking ovarian malignancy diagnosed postoperatively. Preoperative diagnosis is possible if there is a high index of suspicion, obviating extensive surgery and preserving fertility, since long term antibiotic treatment can be completely effective. Pelvic actinomycosis should be included in the differential diagnosis of women presenting a pelvic mass, especially if there is intrauterine device use history.